Catatan Penelitian (Research Note) Production of Seedling of Carica papaya L. by Carica parviplora (A.DC) Solms. Interspecific Hybrids Using Embryo Rescue - A. Ernawati; R. A. Drew; S. W. Adkins; I. D. Godwin (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
A method of embryo rescue to produce seedlings of Carica papaya x Carica parviflora (A. DC) Solms. interspecific hybrids has been developed. Liquid medium of 0.5 Murashige and Skoog nutrients containing kinetin (0.25 µM) and NAA (0.25 µM) was the best medium to germinate the hybrids and produced the biggest leaf area index of the hybrids. Liquid medium of 0.5 MS nutrients containing kinetin (1.0 µM) and NAA (0.25 µM) produced the highest number of leaves of the hybrids, and produced the longest length of hypocotyl of the hybrids.